2020
DOI: 10.1001/jamapediatrics.2019.3869
|View full text |Cite|
|
Sign up to set email alerts
|

Associations Between Screen-Based Media Use and Brain White Matter Integrity in Preschool-Aged Children

Abstract: (AAP) recommends limits on screen-based media use, citing its cognitive-behavioral risks. Screen use by young children is prevalent and increasing, although its implications for brain development are unknown. OBJECTIVE To explore the associations between screen-based media use and integrity of brain white matter tracts supporting language and literacy skills in preschool-aged children. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study of healthy children aged 3 to 5 years (n = 47) was conducted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
185
1
20

Year Published

2020
2020
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(215 citation statements)
references
References 86 publications
9
185
1
20
Order By: Relevance
“…게다 가 강한 시청각적 자극을 장시간 접하게 되면 표현력, 사고력, 추리력, 주의력 부족 등의 문제 (Kwon, 2012;Chonchaiya & Pruksananonda, 2008;Christakis et al, 2004)와 더불어 자극 적인 것에만 반응하는 '팝콘브레인'이 될 수 있다는 우려가 있다 (Cohen, 2011). 특히나 스마트폰, 태블릿PC 등과 같은 스마트미 디어에 과도하게 노출된 유아의 경우 인지능력과 문해능력이 현 저히 떨어진다는 연구도 밝혀진바 있다 (Hutton et al, 2019). 유아의 언어, 인지 발달은 경험과 직접 관련되며 삶에 필요한 가치나 태도를 학습하도록 돕는다 (Mussen et al, 1990).…”
unclassified
“…게다 가 강한 시청각적 자극을 장시간 접하게 되면 표현력, 사고력, 추리력, 주의력 부족 등의 문제 (Kwon, 2012;Chonchaiya & Pruksananonda, 2008;Christakis et al, 2004)와 더불어 자극 적인 것에만 반응하는 '팝콘브레인'이 될 수 있다는 우려가 있다 (Cohen, 2011). 특히나 스마트폰, 태블릿PC 등과 같은 스마트미 디어에 과도하게 노출된 유아의 경우 인지능력과 문해능력이 현 저히 떨어진다는 연구도 밝혀진바 있다 (Hutton et al, 2019). 유아의 언어, 인지 발달은 경험과 직접 관련되며 삶에 필요한 가치나 태도를 학습하도록 돕는다 (Mussen et al, 1990).…”
unclassified
“…A child who abuses devices is deprived of contact with other people, has no opportunity to enrich vocabulary, and does not improve natural communication skills. [Hutton et al, 2019] -deficit of creativity and imagination -the applications available on the tablet or smartphone used by the child are to help cope with boredom. However, they kill creativity and imagination in a child.…”
Section: Consequences Of Smartphone and Tablet Abusementioning
confidence: 99%
“…the area responsible for the development of language and cognitive functions. [Hutton, Dudley, Horowitz-Kraus 2019]…”
Section: Introductionmentioning
confidence: 99%
“…Children under 5 years are a vulnerable population as this is the age where maximum brain growth occurs and increased screen time is associated with adverse neurocognitive outcomes and speech delay. Recent studies with functional cerebral MRI have shown diminished frontal and temporal white matter content in children who were exposed to excessive screen time [4].…”
Section: Introductionmentioning
confidence: 99%